2019
DOI: 10.1111/1365-2435.13473
|View full text |Cite
|
Sign up to set email alerts
|

Multiple facets of diversity effects on plant productivity: Species richness, functional diversity, species identity and intraspecific competition

Abstract: 221. Deciphering the mechanisms that drive variation in biomass production across plant 23 communities of contrasting species composition and diversity is a main challenge of 24 biodiversity-ecosystem functioning research. Niche complementarity and selection effect have 25 been widely investigated to address biodiversity-productivity relationships. However, the 26 overlooking of the specific role played by key species have limited so far our capacity to 27 comprehensively assess the relative importance of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 46 publications
5
82
0
1
Order By: Relevance
“…In a recent study, Karkanis et al (2019) reported that the type of growth substrate (different ratios of peat and perlite) had a significant effect on leaves and stems biomass of S. minor plants with the highest values being recorded for plants grown in sole peat substrate in comparison to plants grown in peat and perlite mixtures. Moreover, considering that the existing reports refer to genetic material from wild ecotypes with great diversity among them, the effect of genotype on agronomic performance has to be considered since complementarity and intra-or inter-specific competition in diversified wild ecosystems may affect plant productivity and selection process in natural environments (Mahaut, Fort, Violle, & Freschet, 2019).…”
Section: Plant Growth Featuresmentioning
confidence: 99%
“…In a recent study, Karkanis et al (2019) reported that the type of growth substrate (different ratios of peat and perlite) had a significant effect on leaves and stems biomass of S. minor plants with the highest values being recorded for plants grown in sole peat substrate in comparison to plants grown in peat and perlite mixtures. Moreover, considering that the existing reports refer to genetic material from wild ecotypes with great diversity among them, the effect of genotype on agronomic performance has to be considered since complementarity and intra-or inter-specific competition in diversified wild ecosystems may affect plant productivity and selection process in natural environments (Mahaut, Fort, Violle, & Freschet, 2019).…”
Section: Plant Growth Featuresmentioning
confidence: 99%
“…These leaf economics spectrum traits predict responses to soil fertility, with increases in mean SLA and decreases in mean LDMC of communities in high nitrogen conditions (Lavorel & Grigulis, 2012;Allan et al, 2015). Leaf economics spectrum traits also predict effects on a number of ecosystem functions, as slow growing communities (with low SLA and high LDMC) typically produce less aboveground biomass and have slow biogeochemical cycling, but may allocate more resources belowground (see Freschet, Swart, & Cornelissen, 2015;Mahaut, Fort, Violle, & Freschet, 2019). Understanding the ways in which community trait values change in response to the environment and affect ecosystem functioning is critical to a mechanistic understanding of global change effects on plant communities and their functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Cultivar and/or species mixtures optimized with respect to functional trait diversity have been discussed recently as being highly important for securing grassland productivity (Mahaut et al ., 2019; Lowry et al ., 2020). One principal question of the current study was whether cultivars of perennial ryegrass representing important functional traits affect forage quality in (i) pure stands and (ii) in mixtures with white clover or white clover and forbs.…”
Section: Discussionmentioning
confidence: 99%